Oxidation of polyphenols in unfermented and partly fermented cocoa beans by cocoa polyphenol oxidase and tyrosinase - Misnawi, .; Selamat, Jinap; Bakar, Jamilah; Saari, Nazamid (Wiley, 2002)
Unfermented and partly fermented dried cocoa beans have an excessively astringent and bitter flavour owing to their high polyphenol content. Studies on the remaining polyphenol oxidase activity and the oxidation of polyphenols in these beans have been conducted in relation to two factors, ie incubation time (0, 1, 2, 4, 8 and 16 h) and pH of incubation (3.5, 4.5, 5.5 and 6.5). Owing to unsuccessful polyphenol oxidation during incubation of partly fermented beans, incubation–enrichment treatments were carried out by combining incubation time (0, 8, 16, 24 and 32 h) and addition of crude cocoa polyphenol oxidase and purified tyrosinase from mushroom at 88 and 8800 units g−1 and pH 5.5. Results showed that the remaining polyphenol oxidase activities of unfermented and partly fermented dried beans were 1 and 0.08% with specific activities of 9 and 1% respectively. The polyphenols of unfermented beans were effectively oxidised by incubation at 45 °C and pH 3.5–6.5 without enzyme enrichment; while those of partly fermented beans required enzyme enrichment. Both crude cocoa polyphenol oxidase and tyrosinase could be used for enzyme enrichment, but tyrosinase seemed to be more effective.